Landmark AIS redevelopment to build on excellence (Ausport, 2003)
New athlete residential accommodation, education and dining facilities • AIS service hub featuring: - improved strength and conditioning gymnasium - indoor testing facility - indoor 120m running track - hydrotherapy and recovery centre - coaches` services centre incorporating AIS management, coaches, performance analysis, athlete and career education - extension of sports science/sports medicine building for physiology and nutrition departments • Aquatic testing and training centre, including a state-of-the-art 50m pool with integrated biomechanics technology • New sport development and education centre • Upgraded AIS training halls • Extended gymnastics hall with expanded training area • Improvements to sports training facilities: - rowing centre - existing pool facility • Provision of a combat training facility